Communicative Role of Preorbital Gland Openings in Captive Banbakri Antelope (Boselaphus tragocamelus, Pallas 1766) in India - Prasad, Suday; Prabhakar, C. S.; Kumar, Amit; Nath, Paras; Ahmad, Reyaz (Research Perspective on Biological Science Vol. 3, 2025)
The preorbital gland is a paired exocrine gland, appearing as a slit-shaped cavity located anterior to the eye. It is found in many ungulates, particularly in the families Bovidae, Cervidae, and various antelope species. Scent marking using the preorbital gland in the Banbakri antelope, also known as the white-footed antelope (Boselaphus tragocamelus), was studied at the Haryana Agriculture Farm, VKS College of Agriculture, Dumraon. This study investigated the behaviour of Banbakri antelopes concerning preorbital gland opening under various conditions, including stress, starvation, and maturity. The research aimed to assess this behaviour as part of a broader investigation into the phenotypic and behavioural characteristics of Banbakri/Nilgai to enhance their well-being and improve resource management. The research is important because it will expand the understanding of this elegant species' behaviour and the functional role of its preorbital gland. Its potential applications in antimicrobial drug development will be explored as well. The behaviour of male and female Banbakri was observed in captivity. During winter, the Banbakri was kept indoors in a 10x20 feet room. Occasionally, it was released into a large outdoor enclosure during summer, winter, and rainy seasons. The enclosure was surrounded by wire fencing approximately 200 by 150 feet (LxW) and 6 feet in height. The enclosure had a savanna. In mature Banbakri antelopes, the preorbital glands measured approximately 2.1 cm in length and 1.0 cm in width. These exocrine glands, appearing as trench-like slits of dark blue to black coloration, were located beneath the eyes. Under free-roaming conditions, both male and female B. tragocamelus rarely exhibited preorbital gland opening. However, the gland was observed to open under stress, particularly when the animal was restrained with a halter for the first time, either at night or occasionally during the day. Preorbital gland opening was also noted during maturity, hunger, and stressful conditions. The findings suggest that this behaviour may serve as a key indicator for differentiating between playful, courtship, and aggressive social behaviours, particularly in stressful situations or stages of maturity. Additionally, the gland may secrete pheromonal substances that facilitate olfactory communication. It can also be said that preorbital gland opening may be an important behavioural indicator of the real maturity of the individual in the sexual context and also in stressful conditions. To the best of our knowledge, no prior studies have reported the opening of the preorbital gland in Banbakri antelopes (B. tragocamelus). This study presents the first recorded observation of this behaviour in captive white-footed antelopes, contributing novel insights into their behavioural ecology. Thus, it can be concluded that this gland opens in Banbakri antelopes under stress, starvation, or sexual maturity contexts, and may serve as an essential behavioural indicator. This could help distinguish between playful, courtship, aggressive, social status, and other behaviours to communicate with other members of Banbakri (Boselaphus tragocamelus).